Pharmacological activity of selected medicinal plants with potential for preventing and treating infectious bovine mastitis, and identification of compounds from active fractions of Kalanchoe gunniae - McGaw, Lyndy Joy (University of Pretoria, 2023)
Thesis (PhD)--University of Pretoria, 2022.